Percepção das alterações no perfil facial de pacientes com má oclusão de classe II tratados com aparelho forsus - Barth, Fernando André (2017)
The purpose of this study was to evaluate the facial profile effects induced by the forsus appliance in the treatment of Class II patients with mandibular deficiency. The sample consisted of 18 young individuals, 3 girls and 15 boys, with Angle Class II malocclusion, treated with forsus appliance associated with fixed corrective orthodontics, with an initial mean age of 12.16 years. The patients selected had to present in their initial and final orthodontic files, lateral radiographs and dental casts. The dental casts were used to quantify Class II malocclusion by the sagittal relationship of the first permanent molars. The radiographic images were exported to the Radiocef program to perform the cephalometric tracing and measurement of some soft tissue variables. Cephalograms obtained from lateral radiographs (pre and post-treatment) were also used to delineate the silhouettes of the patients' profiles, inserted in the same sheet, at random, making it possible to assemble an album with all the patients' silhouettes. These albums were analyzed by three groups of examiners (between 15 and 30 years-old), comprising 45 orthodontists, 45 lay individuals, and 45 orthodontic patients with Class II malocclusion). The three groups were paired by sex. Each examiner rated the facial silhouettes esthetics based on a visual analogue scale (VAS). Comparisons between the facial profiles and between the three groups of examiners were performed with Wilcoxon and Kruskal-Wallis statistics, respectively. Comparisons based on sex of the examiners were performed using Mann-Whitney test. Paired t test was applied to compare cephalometrically the soft issue profile changes before and after treatment. Statistics were performed with a significance level of 5%. Orthodontists (G1) and patients (G3) noticed more evidently the facial changes after orthodontic treatment. Patients rated higher aesthetic scores compared to the other groups. The outcomes were not influenced by sex. Orthodontic treatment performed with forsus combined with fixed orthodontics resulted positively according to orthodontists and patients. The group of individuals with the same characteristics of the treated patients was the one that better pointed out the facial pleasantness of the profiles, indicating a greater acceptability of the inherent characteristics of the Class II facial pattern